Ligand-based discovery of a novel GATA2 inhibitor targeting acute myeloid leukemia cells - Menendez-Gonzalez, Juan Bautista; Strange, Kathryn E.; Bassetto, Marcella; Brancale, Andrea; Rodrigues, Neil P.; Ferla, Salvatore (Frontiers in Drug Discovery, 2022)
Despite major therapeutic advances leading to improved patient outcomes for other haematological malignancies, development of new therapeutics to improve prognosis for acute myeloid leukemia (AML) patients remains an area of unmet clinical need. Overexpression of GATA2, a member of the GATA family of zinc finger transcription factors, has been implicated in AML. In settings where GATA2 is overexpressed in human AML cells, K7174, a proteasome inhibitor that inhibits GATA2, induces apoptosis and enhances the killing activity of AML chemotherapeutics in vitro yet targeting the proteasome has been associated with high toxicity in the clinic. Using an in silico approach, we embarked on a screen to identify specific GATA2 inhibitors that will target AML cells independently of the proteasome. A shape-based virtual screening of an in-house library of small molecules was performed using a low-energy conformation of K7174. The virtual hit compounds were subsequently filtered according to their potential selectivity for GATA2 over the proteasome. From 15 selected compounds evaluated for their ability to kill AML cells in vitro, one compound, an asymmetrical substituted piperazine with Hepatitis C antiviral activity, exhibited superior ability to induce apoptosis and reduce cell cycling in AML cells without proteasome inhibition. This compound was also able to promote cell death of the relapse propagating leukemic stem cell (LSC) compartment while sparing Gata2 knockout LSCs, crucially demonstrating specificity to inhibit GATA2. We have identified a GATA2 specific inhibitor with promising capability to target AML cells in vitro, including LSCs that underpin poor prognosis in AML.